Gender and sexuality in East German film : intimacy and alienation - Frackman, Kyle; Stewart, Faye, 1972- (Screen cultures., 2018)
The cinema of the German Democratic Republic, that is, the cinema of its state-run studio DEFA, portrayed gender and sexuality in complex and contradictory ways. In doing so, it reflected the contradictions in GDR society in respect to such questions. This is the first scholarly collection in English or German to fully address the treatment of gender and sexuality in the productions of DEFA across genres (from shorts and feature films to educational videos, television productions, and documentaries) and in light of social, political, and cultural contexts. It is also unique in its investigation of previously unresearched subjects, including films and directors that have received little scholarly attention and nonconformist representations of gender and sexual embodiments, identifications, and practices. The volume presents the work of leading scholars on the GDR and allows students and scholars to examine East German film with respect to the acceptance, rejection, or nuanced negotiation of ideas of proper male and female behavior espoused by the country's brand of socialism. Contributors: Muriel Cormican, Jennifer L. Creech, Heidi Denzel de Tirado, Kyle Frackman, Sebastian Heiduschke, Sonja E. Klocke, John Lessard, Larson Powell, Victoria I. Rizo Lenshyn, Reinhild Steingröver, Faye Stewart, Evan Torner, Henning Wrage. Kyle Frackman is Assistant Professor of Germanic Studies at the University of British Columbia. Faye Stewart is Associate Professor of German at Georgia State University.